Evaluation of Education of The Use of Anthropometer Elderly Seats in Reducing Musculoskeletal Complaints and Improving The Elderly Satisfaction of Elderly in Posyandu - Lestari, Agus Sri; Ribek, Nyoman; Rosmalawati, Dwi; Gama, Kt (LPPM Undiksha, 2019)
The background of the study was that the number of elderly people in the world and Indonesia in particular had increased and was a burden if their health conditions were not given enough attention. One of the issues of concern is the educational evaluation of the use of elderly anthropometer chairs can increase the comfort feeling of the elderly. The purpose of this study was to determine whether the educational use of anthropometer elderly chairs can reduce musculoskeletal complaints and increase the feeling of comfort in the elderly.The study was conducted at the Posyandu of Tumbak Bayuh Mengwi Village, Badung Regency, Bali Province and in the Posyandu RW 12, Bedali Village, UPT, Lawang Public Health Center, Malang Regency because they have similar characteristics. The method used is experimental (quasi experiment) using the same design as the subject (treatment by subject design). The results of the study concluded that musculoskeletal complaints in the initial condition with analysis using the t-pair test, obtained insignificant results (p> 0.05), meaning that there was no difference between the initial conditions. Analysis Test the difference in the final condition (post) obtained significant results (p * <0.05) meaning that there is a difference between the final condition and the t-pair test analysis on comfort shows a value of p <0.05, meaning that the elderly shows a sense of comfort using elderly anthropometer chair. Recommended for Puskesmas in posyandu to have anthropometer elderly chairs and educate their use in the elderly.